2018
DOI: 10.1002/cbdv.201800215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Cytotoxicity of the Cobalt (III) Complex with N,N‐Diethyl‐4‐(2,2′:6′,2′′‐terpyridin‐4′‐yl)aniline

Abstract: A cobalt(III) complex, [Co(L) ](ClO ) (1), in which the ligand L was N,N-diethyl-4-(2,2':6',2''-terpyridin-4'-yl)aniline (L), was synthesized and fully characterized. This new cobalt(III) complex 1 exhibited selective cytotoxicity against HeLa, T-24, A549, MGC80-3, HepG2, and SK-OV-3 cells with IC values in the micromolar range (0.52 - 4.33 μm), and it exhibited low cytotoxicity against normal HL-7702 cells. The complex 1 was the most potent against the T-24 cells. It was found that 1 could cause the cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…20 Qin and co-workers showed that a Co(III) complex of a substituted terpyridine induced G1-phase apoptosis in bladder cancer cells, with a mechanism involving mitochondrial membrane depolarization, caspase-3 and caspase-9 activation, and an increase in intracellular Ca 2+ levels. 21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Qin and co-workers showed that a Co(III) complex of a substituted terpyridine induced G1-phase apoptosis in bladder cancer cells, with a mechanism involving mitochondrial membrane depolarization, caspase-3 and caspase-9 activation, and an increase in intracellular Ca 2+ levels. 21…”
Section: Introductionmentioning
confidence: 99%
“…Each of these complexes was shown to induce differentiation in all-trans retinoic acid-resistant acute myeloid leukemia cells, and each was cytotoxic toward cervical cancer cells, with the O-donor and S-donor complexes inducing apoptosis by DNA damage from ROS generated by Fenton-type reactions and by G2/M cell cycle arrest, respectively . Qin and co-workers showed that a Co­(III) complex of a substituted terpyridine induced G1-phase apoptosis in bladder cancer cells, with a mechanism involving mitochondrial membrane depolarization, caspase-3 and caspase-9 activation, and an increase in intracellular Ca 2+ levels …”
Section: Introductionmentioning
confidence: 99%